ANALISIS KESALAHAN SISWA SMP DALAM MENYELESAIKAN SOAL KOMUNIKASI MATEMATIS PADA MATERI PERSAMAAN DAN PERTIDAKSAMAN LINEAR SATU VARIABEL BERDASARKAN KATEGORI KESALAHAN MENURUT WATSON - Oktaviani, Rani; Salbiah, Anita Oktavia; Hidayat, Wahyu; Rohaeti, Euis Eti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2019)
This study aims to determine the ability of students mathematical communication skills of junior high school students in the material of One Variable Linear Equation and Inequality. The study was conducted on seventh grade students in one of the junior high schools in Cimahi as many as 37 students who were taken 6 random samples based on the results of the location of errors done by students in different criteria according to Watson's error. The research approach used is qualitative with descriptive method. The instrument used is a matter of mathematical communication that has been validated. Tests carried out by students were examined for the type of error based on the Watson category and an analysis of error answers was carried out. The results showed that based on the percentage of the types of errors students who had completed mathematical communication problems based on the category of errors according to Watson were incorrect data / ID errors included in a small error of 21%, improper procedure errors IP) is included in a high error of 46%. Omitted conclusions (OC) fall into a fairly low error of 3%. Errors in data missing (ommited data / OD) which is equal to 21%, Error hierarchical problem (SHP) problem is 7%. While conflict response levels (response level conflict / RLC), indirect manipulation (UM), and also errors other than the seven above other / AO) are 0% each, including very low errors.